2011
DOI: 10.1038/ejcn.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns, subclinical inflammation, incident coronary heart disease and mortality in middle-aged men from the MONICA/KORA Augsburg cohort study

Abstract: Background/Objectives: We aimed to identify dietary patterns associated with inflammatory markers and to examine their impact on the incidence of coronary heart disease (CHD) and all-cause mortality, as subclinical inflammation is a risk factor for these outcomes. Subjects/Methods: The study population comprised 981 middle-aged men participating in the first or third 'MONItoring of Trends and Determinants in CArdiovascular Diseases' (MONICA) Augsburg surveys who completed 7-day dietary records. Subjects were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…In contrast, dietary patterns rich in red meat and sugar-rich foods have been associated with an increased risk of mortality, type 2 diabetes mellitus and CHD in studies that defined these patterns a posteriori (17)(18)(19)(20)25,28,31,32,35,(37)(38)(39) . There is a general agreement on the potential deleterious effect of higher intakes of these two food items and most of the dietary guidelines and scores designate these foods as unfavourable components (Table 1).…”
Section: Nutrition and Healthy Ageing: Agreement On The Key Ingredientsmentioning
confidence: 99%
“…In contrast, dietary patterns rich in red meat and sugar-rich foods have been associated with an increased risk of mortality, type 2 diabetes mellitus and CHD in studies that defined these patterns a posteriori (17)(18)(19)(20)25,28,31,32,35,(37)(38)(39) . There is a general agreement on the potential deleterious effect of higher intakes of these two food items and most of the dietary guidelines and scores designate these foods as unfavourable components (Table 1).…”
Section: Nutrition and Healthy Ageing: Agreement On The Key Ingredientsmentioning
confidence: 99%
“…Greater consumption of a comparable pattern derived by reduced rank regression (high in meat, soft drinks, beer and lower in vegetables, fruits, whole-meal bread, cereals, dairy products) increased risk for CAD and CVD mortality in a German cohort. In this study, adjustment for smoking status, which was considered as a confounder, attenuated the findings; however, stratified analyses were not conducted [91].…”
Section: Associations Of a Posteriori Dietary Patterns And Smoking Stmentioning
confidence: 91%
“…First, it is well established that smoking confounds the association between diet and CVD. Thus, all studies reviewed adjusted for smoking in their analysis [35,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][87][88][89][90][91][92][93][94][95][96][97] and showed that the effect of diet is attenuated when smoking is considered [73,91]. However, as discussed, smoking may interact with diet and modify the effect of diet on CVD, which has been an increasing focus of more recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations